2019
DOI: 10.1007/s00122-019-03453-7
|View full text |Cite
|
Sign up to set email alerts
|

Aphid resistance in Capsicum maps to a locus containing LRR-RLK gene analogues

Abstract: Key message A QTL for aphid resistance on pepper chromosome 2 was identified and validated. This QTL affects aphid survival and reproduction, and was fine mapped to a locus containing LRR-RLK analogues. Abstract Myzus persicae is one of the most threatening insect pests that adversely affects pepper (Capsicum) cultivation. Resistance to aphids was previously identified in Capsicum baccatum. This study aimed at elucidating the genetics of aphid resistance in C. baccatum. A QTL analysis was carried out for M. pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The receptor-like kinases (RLKs) are plant extracellular receptors involved in pathogen recognition and the subsequent activation of plant defense responses [45,46]. The Arabidopsis LRR RECEPTOR-LIKE PROTEIN KINASES modulates brassinosteroid, abscisic acid, SA , and Ca2 + signaling , and positively regulates diverse responses against stresses such as pathogen infection, cold, salt , and aphid attacks [47,48]. In maize, a WALL-ASSOCIATED RECEPTOR-LIKE KINASE was found to confer quantitative field resistance against most Northern corn leaf blights [46].…”
Section: The Transcriptional Change In Npr1-2 Transgenic Linementioning
confidence: 99%
“…The receptor-like kinases (RLKs) are plant extracellular receptors involved in pathogen recognition and the subsequent activation of plant defense responses [45,46]. The Arabidopsis LRR RECEPTOR-LIKE PROTEIN KINASES modulates brassinosteroid, abscisic acid, SA , and Ca2 + signaling , and positively regulates diverse responses against stresses such as pathogen infection, cold, salt , and aphid attacks [47,48]. In maize, a WALL-ASSOCIATED RECEPTOR-LIKE KINASE was found to confer quantitative field resistance against most Northern corn leaf blights [46].…”
Section: The Transcriptional Change In Npr1-2 Transgenic Linementioning
confidence: 99%
“…The LRR-RLK type proteins are implicated in aphid resistance in pepper (Capsicum baccatum L.) to the green peach aphid (M. persicae) (Sun et al, 2020) and in melon (Cucumis melo L.) to the cotton-melon aphid (A. gossypii) (Klingler et al, 2001). In other host-aphid systems, coiledcoil nucleotide-binding site LRR (CC-NBS-LRR) subfamilies of resistant proteins are implicated in aphid resistance.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the genetics of quantitative traits of a phenotypically resistant line against biotic and abiotic stresses, genome-wide association studies (GWAS) are widely used as a powerful molecular tool in plant breeding and crop improvement programs to identify molecular markers such as single nucleotide polymorphisms (SNPs) that are closely linked to the genomic regions that control traits of interest in the host plant. A GWAS approach excels in detection of quantitative trait loci (QTL) associated with pest and disease resistance when germplasm of a specific crop with a wide and diverse genetic background is used (Bastien et al, 2014;Barmukh et al, 2020;Sun et al, 2020). Several genetic association studies have been reported in lentil for agronomic, pathological, or environmental traits such as QTL of winter hardiness genes (Kahraman et al, 2004), milling traits (Subedi et al, 2018), seed weight and seed size (Sudheesh et al, 2016), or resistance to ascochyta blight (Tullu et al, 2006) and aphanomyces root rot (Ma et al, 2020).…”
mentioning
confidence: 99%
“…Next to interspecific variation between Brassicaceae species we also identified intraspecific variation in HRlike cell death among accessions of several species [11,21], suggesting that genetic analysis to identify casual loci should be feasible. Up to now, classical forward genetics, such a linkage mapping and/or GWAS, helped to identify quantitative trait loci (QTLs) involved in both upstream (perception) and downstream mechanisms associated with plant resistance to insect feeding [15,[52][53][54][55][56]. Currently, genetic mapping efforts in Brassica crop species are increasingly made possible given a growing availability of high quality genomic and genetic resources [57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%